Testosterone Deprivation Aggravates Left-Ventricular Dysfunction in Male Obese Insulin-Resistant Rats via Impairing Cardiac Mitochondrial Function and Dynamics Proteins - Nattayaporn Apaiajai (2018)
© 2018 S. Karger AG, Basel. All rights reserved. Background: We have previously reported that testosterone deprivation at a very young age accelerated, but did not aggravate, left-ventricular (LV) dysfunction in obese insulin-resistant rats. However, the effects of testosterone deprivation during adulthood on LV function in obese insulin-resistant rats remains unclear. We hypothesized that testosterone deprivation aggravates LV dysfunction and cardiac autonomic imbalance via the impairment of cardiac mitochondrial function and dynamics proteins, a reduction in insulin receptor function, and an increase in apoptosis in obese insulin-resistant rats. Methods: Male rats were fed on either a normal diet (ND) or a high-fat diet (HFD) for 12 weeks. They were then subdivided into 2 groups: Sham operation (NDS, HFS) and orchiectomy (NDO, HFO). Metabolic parameters, blood pressure, heart rate variability (HRV), and LV function were determined at baseline and before and after orchiectomy. Mitochondrial function and dynamics proteins, insulin signaling, and apoptosis were determined 12 weeks postoperatively. Results: HFS rats exhibited obese insulin resistance, depressed HRV, and LV dysfunction. In HFO rats, systolic blood pressure was increased with more excessive depression of HRV and increased LV dysfunction, compared with HFS rats. These adverse cardiac effects were consistent with markedly increased mitochondrial dysfunction, reduced mitochondrial complex I and III proteins, reduced mitochondrial fusion proteins, and increased apoptosis, compared with HFS rats. However, testosterone deprivation did not lead to any alteration in the insulin-resistant condition in HFO rats, compared with HFS rats. Conclusion: We concluded that testosterone deprivation during adulthood aggravated the impairment of mitochondrial function, mitochondrial respiratory complex, mitochondrial dynamics proteins, and apoptosis, leading to LV dysfunction in obese insulin-resistant rats.